Seedling Chloroplast Responses Induced by N-Linolenoylethanolamine Require Intact G-Protein Complexes - Yan, Chengshi (Plant Physiol, 2020)
In animals, several long-chain N-acylethanolamines (NAEs) have been identified as endocannabinoids and are autocrine signals that operate through cell surface G-protein–coupled cannabinoid receptors. Despite the occurrence of NAEs in land plants, including nonvascular plants, their precise signaling properties and molecular targets are not well defined. Here we show that the activity of N-linolenoylethanolamine (NAE 18:3) requires an intact G-protein complex. Specifically, genetic ablation of the Gβγ dimer or loss of the full set of atypical Gα subunits strongly attenuates an NAE-18:3–induced degreening of cotyledons in Arabidopsis (Arabidopsis thaliana) seedlings. This effect involves, at least in part, transcriptional regulation of chlorophyll biosynthesis and catabolism genes. In addition, there is feedforward transcriptional control of G-protein signaling components and G-protein interactors. These results are consistent with NAE 18:3 being a lipid signaling molecule in plants with a requirement for G-proteins to mediate signal transduction, a situation similar, but not identical, to the action of NAE endocannabinoids in animal systems.